Analysis of microstructure, kinetics of isothermal solidification and mechanical properties of IN718/MBF-20/SS316L TLP joints. Issue 15 (3rd August 2021) - Emami, Mohammad; Binesh, Behzad; Heydarzadeh, Javid M.
ABSTRACT: In this research, transient liquid phase (TLP) bonding of IN718 and SS316L dissimilar alloys was carried out using MBF-20 amorphous interlayer. The effects of bonding temperature and time ranging from 1030°C to 1110°C and 1–30 min on the microstructure and mechanical properties of the bonded samples were studied. The mechanism of the microstructure formation and the solidification sequence at the joint area were discussed. Two diffusion models assuming stationary and moving solid/liquid interface were used to study the isothermal solidification kinetics and the time required for the complete isothermal solidification (tf ) at different temperatures was predicted. The results suggest that the tf values obtained by the moving interface approach are closer to those of the experiments. The minimum difference between the experimental value of tf and that calculated by the moving interface approach was about 26%, while it was about 106% by considering the stationary interface approach. A more uniform hardness distribution across the joint area and the highest shear strength values were observed in the samples with complete isothermal solidification. The maximum shear strength of 440 MPa was obtained for the sample bonded at 1030°C for 30 min. This was attributed to the formation of a eutectic-free joint in these samples.